In vivo evaluation of bioprinted cardiac patches composed of cardiac-specific extracellular matrix and progenitor cells in a model of pediatric heart failure. (8th December 2021) - Bejleri, Donald; Robeson, Matthew J.; Brown, Milton E.; Hunter, Jervaughn; Maxwell, Joshua T.; Streeter, Benjamin W.; Brazhkina, Olga; Park, Hyun-Ji; Christman, Karen L.; Davis, Michael E.
Abstract : Patches composed of cardiac-specific extracellular matrix and progenitor cells were implanted in a model of heart failure. Matrix inclusion was the most influential parameter driving cardiac therapeutic improvements, with or without cell inclusion. Abstract : Pediatric patients with congenital heart defects (CHD) often present with heart failure from increased load on the right ventricle (RV) due to both surgical methods to treat CHD and the disease itself. Patients with RV failure often require transplantation, which is limited due to lack of donor availability and rejection. Previous studies investigating the development and in vitro assessment of a bioprinted cardiac patch composed of cardiac extracellular matrix (cECM) and human c-kit + progenitor cells (hCPCs) showed that the construct has promise in treating cardiac dysfunction. The current study investigates in vivo cardiac outcomes of patch implantation in a rat model of RV failure. Patch parameters including cECM-inclusion and hCPC-inclusion are investigated. Assessments include hCPC retention, RV function, and tissue remodeling (vascularization, hypertrophy, and fibrosis). Animal model evaluation shows that both cell-free and neonatal hCPC-laden cECM-gelatin methacrylate (GelMA) patches improve RV function and tissue remodeling compared to other patch groups and controls. Inclusion of cECM is the most influential parameter driving therapeutic improvements, with or without cell inclusion. This study paves the way for clinical translation in treating pediatric heart failure using bioprinted GelMA-cECM and hCPC-GelMA-cECM patches.